A photoactive injectable antibacterial hydrogel to support chemo-immunotherapeutic effect of antigenic cell membrane and sorafenib by near-infrared light mediated tumor ablation. (April 2023) - Abbaszadeh, Samin; Eskandari, Mohammad Reza; Nosrati-Siahmazgi, Vahideh; Musaie, Kiyan; Mehrabi, Soraya; Tang, Ruikang; Jafari, Mohammad Reza; Xiao, Bo; Hosseinpour Sarmadi, Vahid; Haghi, Fakhri; Chen, Bo Zhi; Guo, Xin Dong; et al.
Abstract: Intravenously administered nanocarriers suffer from off-target distribution, pre-targeting drug leakage, and rapid clearance, limiting their efficiency in tumor eradication. To bypass these challenges, an injectable hydrogel with time- and temperature-dependent viscosity enhancement behavior and self-healing property are reported to assist in the retention of the hydrogel in the tumor site after injection. The cancer cell membrane (CCM) and sorafenib are embedded into the hydrogel to elicit local tumor-specific immune responses and induce cancer cell apoptosis, respectively. In addition, hyaluronic acid (HA) coated Bi2 S3 nanorods (BiH) are incorporated within the hydrogel to afford prolonged multi-cycle local photothermal therapy (PTT) due to the reduced diffusion of the nanorods to the surrounding tissues as a result of HA affinity toward cancer cells. The results show the promotion of immunostimulatory responses by both CCM and PTT through the release of inflammatory cytokines from immune cells, which allows localized and complete ablation of the breast tumor in an animal model by a single injection of the hydrogel. Moreover, the BiH renders strong antibacterial activity to the hydrogel, which is crucial for the clinical translation of injectable hydrogels as it minimizes the risk of infection in the post-cancer lesion formed by PTT-mediated cancer therapy. Graphical abstract: Image 1